How Good EFL Learners Decrease Their Foreign Language Anxiety: A Solution for the EFL Students with High Anxiousness - Ali Wira Rahman (Universitas Cokroaminoto Palopo, 2017)
This research is aimed to find out the solution of the anxiousness phenomenon that always attacks the EFL Learners particularly in Indonesia. In the future, this research is expected as main information for all students and lecturer or teachers of English to decrease the students’ anxiety in performing speaking. In long time ago until now, it becomes a big problem for all beginner students of English. The implementation of this research starting by doing observation to all class in the sixth semester students to find out some good EFL Learners. Researchers then consulting with the lecturer in determining the students to be the subject of this research. After finding the subject, interview session will be conducted to find out several information about their anxiousness. The data will be collected until limit of saturation. The last step of this research is doing analysis of the data were taken from observation and interview. The researchers will apply data reduction for the first step, the second is data display and the last will be drawing conclusion and verification of the data. The conclusion that being made will be verify by triangulation to get the validity of the result of this research.